Sistem Pendukung Keputusan Pemilihan Menu Makanan bagi Anak dengan Metode Analitycal Hierarchy Process (AHP) - Yustria Handika Siregar; Sri Rahayu (Universitas Asahan, 2018)
Abstract - Selection of a good food menu for children is a factor that needs to be considered to optimize the growth of the baby. In this case, the role of parents is needed in the selection of good food for children. The food menu needed for children must contain balanced nutrients such as carbohydrates, protein, fiber content, and water. As is the case with children in the Taqwa Perkebunan Gunung Melayu Kindergarten where the regulation of diet in children is very dependent on the knowledge of the mother in choosing, processing and managing the food needed for the child's school supplies. For this reason, a decision support system is needed in determining the ranking of healthy food menus using the AHP method. The AHP method helps in decision making through complex comparisons to be a more accurate alternative. This method also allows measurement of ratio scales for alternative criteria and scoring weights. So that a solution is obtained or the results of several alternatives for a decision to be taken. With the existence of a decision support system, the selection of food menus for children is expected to help parents choose food menus quickly and according to the needs of children. Keywords - Food Menu, Decision Support System, AHP